Assessment of oxidative stress status and neuroprotection by vitamin E in chronic cerebral hypoperfusion-induced neurodegeneration in rats - Saxena, Anil Kumar; A.Talib, Norlelawati; Azzubaidi, Marwan Saad; Sayeed, Sayyada (IIUM, 2015)
Background: A persistent reduction in regional cerebral blood flow (CBF) compromises memory and cognitive functions in the elderly leading to neurological illnesses. To unravel the neuropathological consequences of a reduced CBF, a similar condition has been created in rats by common carotid artery occlusion (2 vessel occlusion, 2VO). Oxidative stress, caused due to a disproportionate release of reactive oxygen species (ROS), has been associated with neuronal cell death in various regions of the brain.